Effects of transluminal balloon angioplasty and stenting on the clinical course of ischemic chronic heart failure with preserved or reduced left ventricular ejection fraction: radionuclide 4D tomoventriculography data - N. V. Shashkova; S. N. Tereshchenko; L. E. Samoylenko; D. F. Satlykova; A. M. Gerasimov (Кардиоваскулярная терапия и профилактика)
Aim. To study the effects of transluminal balloon angioplasty (TLBAP) and stenting on right and left ventricular (RV, LV) hemodynamics, as well as on long-term clinical prognosis, in patients with ischemic chronic heart failure (CHF). Material and methods. In 20 patients with ischemic CHF, Functional Class (FC) II–III (NYHA), radionuclide 4D tomoventriculography (4D-RTVG) was performed at baseline and 6 and 12 months after TLBAP, in order to assess cardiac hemodynamics. Based on ejection fraction (EF) values, all participants were divided into two groups. Group I (n=10; mean age 57,2 (2,7) years) included men with EF <45%, FC II–III CHF, and mean CHF duration of 3,1 (0,6) years. Group II (n=10; mean age 62,6 (2,7) years) included 5 men and 5 women with EF >45%, FC II CHF, and CHF duration of 2 (0,4) years. Results. Twelve months after TLBAP, Group I demonstrated a significant increase in stroke volume (SV), LV EF, and RV EF, as well as an improvement in LV maximum ejection velocity (MEV), maximum filling velocity (MFV), and maximum filling time (MFT), as well as in LV and RV one-third filling fraction (1/3 FF) (p<0,05). A decrease in LV enddiastolic volume (EDV), LV end-systolic volume (ESV), and RV ESV, some increase in RV EDV, and an improvement in RF MEV, MFV, and MFT were non-significant (p>0,05). In Group II, an increase in LV SV and LV EF, as well as an improvement in RV 1/3FF and MFT, was statistically significant (p<0,05). At the same time, an increase in RF SV, EF, EDV, and ESV, as well as an improvement in LV and RV MEV and MFV, LV 1/3FF and LV MFT, without any substantial changes in LV EDV and ESV, lacked statistical significance (p>0,05). Cardiac hemodynamic changes were associated with improved quality of life (QoL) and reduced CHF FC and angina FC. Conclusion. TLBAP and stenting facilitated an increase in EF and SV, an improvement in LF and RF systolic and diastolic function, an improvement in QoL and exercise capacity, and a reduction in CHF FC and angina FC.